313 UP-REGULATION OF ALKALINE PHOSPHATASE IN THE AORTA MAY CONTRIBUTE TO VESSEL CALCIFICATION IN UREMIC RATS. (1st January 2006) - Lomashvili, K. A.; Garg, P.; O'Neill, W. C.
Abstract : We have previously shown that pyrophosphate (PPi) is an important endogenous inhibitor of medial vascular calcification. Calcification can be induced in intact vessels in culture only after removal of PPi. This suggests that a deficiency of PPi, due either to decreased production or increased degradation, could explain vascular calcification in renal failure. Pyrophosphate can be hydrolyzed by inorganic pyrophosphatase or alkaline phosphatase (alk p).We therefore examined the effect of uremia on PPi degradation. Alk p induces calcification in culture and could also play a pathogenetic role in vessel calcification in vivo. We investigated effects of uremia in vivo. We also investigated influence of uremic plasma, parathyroid hormone, and calcitriol, as well as [Ca] and [PO4 ] on the PPi degradation and alkaline phosphatase activity in rat aortas in culture. Aortic rings from control and uremic rats were cultured in DMEM containing 1.8 mM Ca and 0.9 mM PO4. Uremia was produced by an adenine diet for 4 weeks and controls were pair-fed normal rat chow. Alk p activity in intact vessels was measured as hydrolysis of p-nitrophenylphosphate (p-NP) and the rate of PPi hydrolysis was measured using 32 PPi. The rate of p-NP hydrolysis by intact aorta in culture was pH dependent in a manner consistent with alk p. PPi hydrolysis was 60% greater and alk p activity 100% greater in uremic rats vs normal rats. Similar results were obtained when normal aortas cultured with uremic serum. PTH, calcitriol, and high [PO4 ] or high [Ca] up-regulated alk p 2- to 3-fold in aortas from normal rats. These results indicate that humoral circulatory factors may up-regulate vascular alk p activity in vessels in uremia and could promote calcification by increasing pyrophosphate hydrolysis. PTH, calcitriol, [Ca], and [PO4 ] also up-regulate alk p and could contribute to calcification.